Transfer Ribonucleic Acid in KB Cells Infected with Adenovirus Type 2 - Raška, Karel (1970)
Populations of transfer ribonucleic acid (tRNA) extracted from control and type 2 adenovirus (Ad2)-infected KB cells were compared. No consistent differences in acceptor activity for 11 amino acids were observed. Comparison of methylated albumin-kieselguhr (MAK) elution profiles of arginyl-tRNA from control and infected cells revealed a minor modification in that the proportion of arginyl-tRNA eluting at high salt concentration was somewhat greater in infected cells. No similar differences were observed in MAK elution profiles of aspartyl-, isoleucyl-, leucyl-, phenylalanyl-, seryl-, tyrosyl-, and valyl-tRNA. Hybridization of 4S RNA from infected cells labeled by incorporation of (3)H-uridine with Ad2 deoxyribonucleic acid revealed the presence of a complementary species of RNA in this preparation. Hybridization of (3)H-arginyl-tRNA and of (3)H-aminoacyl-tRNA labeled by charging with (3)H-arginine or a (3)H-mixture of amino acids, respectively, failed to detect the presence of virus-specific tRNA in Ad2-infected cells.